2016
DOI: 10.21070/picecrs.v1i1.641
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cooperative Learning in Enhancing Students’ Writing Skills in Pakistani Colleges: A Review of Literature

Abstract: ABSTRACT:The current study examined the causes of poor writing skills of intermediate students in the public sector colleges of Pakistan. Besides, the study discusses the methods being used in these colleges and how those methods can be replaced by cooperative and collaborative learning techniques to enhance the writing skills of the students successfully and effectively. Research conducted so far in Pakistani context indicated that a large number of students in Pakistan fail due mainly to their poor writing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The findings of this study showed that the utilization of the STAD method was beneficial to enhance the quality of the teaching and learning process, especially in teaching descriptive writing. These findings also support the studies done by Zulfa (2015); Mahmoud and Mohamed (2014) and Siddique and Singh (2016) who had verified that the STAD method can improve students" writing performance significantly.…”
Section: Samplingsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study showed that the utilization of the STAD method was beneficial to enhance the quality of the teaching and learning process, especially in teaching descriptive writing. These findings also support the studies done by Zulfa (2015); Mahmoud and Mohamed (2014) and Siddique and Singh (2016) who had verified that the STAD method can improve students" writing performance significantly.…”
Section: Samplingsupporting
confidence: 89%
“…Similarly Siddique and Singh (2016) employed the cooperative learning method to teach ESL writing skills to college students (intermediate) in Pakistan. The findings indicated that students" descriptive essay writing improved tremendously through this method.…”
Section: The Stad Methods and Academic Achievementmentioning
confidence: 99%
“…After the analysis of both qualitative and quantitative data, the result shows that CL is effective in improving learners' ELP level. This result is consistent with the previous research (see Ahmadi, Motallebzade, & Fatemi, 2014;Aicha, 2012;Almuslimi, 2016;Al-Tamimi & Attamimi, 2014;Chukwuyenum, Nwankwo, & Toochi, 2014;Keshavarz, Shahrokhi, & Nejad, 2014;Khan & Ahmad, 2014;Lin, 2009;Mohammadi & Davarbina, 2015;Ning, 2010;Siddique & Singh, 2016;Soraya, 2010). But, the peer-mediated model of learning is criticized to be a "failure to address the needs of the more able pupil who may require more independent learning and flexibility" (Jolliffe, 2007, p. 14).…”
Section: Discussionsupporting
confidence: 91%
“…There has been much research done on CL (see Ahmadi, Motallebzade, & Fatemi, 2014;Aicha, 2012;Almuslimi, 2016;Al-Tamimi & Attamimi, 2014;Chukwuyenum, Nwankwo, & Toochi, 2014;Keshavarz, Shahrokhi, & Nejad, 2014;Khan & Ahmad, 2014;Lin, 2009;Mohammadi & Davarbina, 2015;Ning, 2010;Siddique & Singh, 2016;Soraya, 2010). However, no research is found to have been carried out to investigate the effectiveness of CL for the improvement of learners' English language proficiency level in the context of Nepal.…”
Section: Neltamentioning
confidence: 99%
“…It makes the class a studentcentred where they can discuss, share and construct their own sentences of varied structures. [11] Therefore, writing learning needs self-concept. Like as Fatimawati found in her research that in the academic writing class.…”
Section: Graph 1 the Increasing English Essay Writing Testmentioning
confidence: 99%